The nth term rule of the given quadratic sequence is needed.
The nth term rule is [tex]T_n=n^2+3n+2[/tex]
The quadratic sequence is
[tex]6,12,20,30,42,56,72[/tex]
We know the sequence is quadratic so the general sequence will be of the form
[tex]T_n=an^2+bn+c[/tex]
For [tex]n=1,2,3[/tex] the general terms will be
[tex]T_1=a+b+c=6[/tex]
[tex]T_2=4a+2b+c=12[/tex]
[tex]T_3=9a+3b+c=20[/tex]
[tex]T_2-T_1=3a+b\\\Rightarrow 3a+b=6[/tex]
[tex]T_3-T_2=5a+b\\\Rightarrow 5a+b=8[/tex]
Subtracting the above equations
[tex]T_2-T_1-(T_3-T_2)=3a+b-(5a+b)\\\Rightarrow 6-8=-2a\\\Rightarrow -2=-2a\\\Rightarrow a=\dfrac{-2}{-2}=1[/tex]
Finding [tex]b[/tex] and [tex]c[/tex]
[tex]3a+b=6\\\Rightarrow b=6-3a=6-3\times 1\\\Rightarrow b=3[/tex]
[tex]a+b+c=6\\\Rightarrow c=6-a-b=6-1-3\\\Rightarrow c=2[/tex]
So,
[tex]a=1[/tex], [tex]b=3[/tex] and [tex]c=2[/tex]
Substituting in [tex]T_n[/tex]
[tex]T_n=n^2+3n+2[/tex]
Learn more:
https://brainly.com/question/12328748
https://brainly.com/question/12328522